2019
DOI: 10.3389/fpsyg.2019.00680
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Validation of the PICCOLO (Parenting Interactions With Children: Checklist of Observations Linked to Outcomes)

Abstract: Background/Objective: The aim of this study was to explore the psychometric properties of the Spanish version of the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO; Roggman et al., 2013a ). This observational measure is composed of 29 items that assess the quality of four domains of parenting interactions that promote child development: affection, responsiveness, encouragement, and teaching. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 62 publications
5
35
0
1
Order By: Relevance
“…The Spanish version of the PICCOLO was recently validated using a sample of 203 mother–child dyads [ 93 ]. The results of the confirmatory factor analysis confirmed that the instrument has a four-factor structure of first order domains (Affection, Responsiveness, Encouragement, and Teaching) that collapses into a single, second-order factor (parenting).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spanish version of the PICCOLO was recently validated using a sample of 203 mother–child dyads [ 93 ]. The results of the confirmatory factor analysis confirmed that the instrument has a four-factor structure of first order domains (Affection, Responsiveness, Encouragement, and Teaching) that collapses into a single, second-order factor (parenting).…”
Section: Methodsmentioning
confidence: 99%
“…The Spanish version [93] of the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO) [17,18] was used to assess parenting. The PICCOLO is a reliable and valid 29-item measure of parent-child interactions for parents with children between the ages of 10 and 47 months.…”
Section: Instrumentsmentioning
confidence: 99%
“…Indeed, several studies suggest that parental well-being is linked with the quality of parenting even in the presence of neurodevelopmental conditions [9,10]. Caregivers are well-recognized as the primary source of prevention and care for children [11] and they can provide relevant stimulation to promote long-term cognitive, language and socio-emotional development up to preschool-and school-age [6,12,13]. Early familycentered interventions for children that actively engage parents have been found to be the most beneficial for children's development [14,15] and the most rewarding for the healthcare systems in terms of economic returns [16].…”
Section: Introductionmentioning
confidence: 99%
“…31 Notably, both paternal and maternal caregiving is associated with better cognitive and language development in preschoolers with ND. 32 As such, early supportive interventions directed at improving the quality of parental sensitivity and parent-infant interaction should be a priority in the population of children diagnosed with ND. 33 34 The video-feedback intervention (VFI) is an early parent-child focussed intervention that aims to promote positive and sensitive parenting and, indirectly, support infants' behavioural and socio-emotional development.…”
Section: Open Accessmentioning
confidence: 99%
“… 15 29 30 Parental sensitivity and teaching are associated with the developmental quotient of 23- to 47-month-old children with diverse ND conditions. 31 Notably, both paternal and maternal caregiving is associated with better cognitive and language development in preschoolers with ND. 32 As such, early supportive interventions directed at improving the quality of parental sensitivity and parent-infant interaction should be a priority in the population of children diagnosed with ND.…”
Section: Introductionmentioning
confidence: 99%